Co-infection With Chromosomally-Located blaCTX-M-14 and Plasmid-Encoding blaCTX-M-15 in Pathogenic Escherichia coli in the Republic of Korea - Park, Jungsun; Shin, Eunkyung; Park, Ae Kyung; Kim, Soojin; Jeong, Hyun Ju; Kim, Jin Seok; Jin, Young-Hee; Park, Nan Joo; Chun, Jeong-hoon; Hwang, Kyujam; Lee, Kwang Jun; Kim, Junyoung (Frontiers in Microbiology, 2020)
The emergence of third-generation cephalosporin resistance in Escherichia coli is increasing at an alarming rate in many countries. Thus, the aim of this study was to analyze co-infecting blaCTX-M-producing pathogenic E. coli isolates linked to three school outbreaks. Among 66 E. coli isolates, 44 were identified as ETEC O25, an ETEC isolate serotype was O2, and the other 21 were confirmed as EAEC O44. Interestingly, six patients were co-infected with EAEC O44 and ETEC O25. For these isolates, molecular analysis [antibiotic susceptibility testing, identification of the β-lactamase gene, multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE)] was performed for further characterization. In addition, the transmission capacity of blaCTX-M genes was examined by conjugation experiments. Whole-genome sequencing (WGS) was performed on representative EAEC O44 and ETEC O25 isolates associated with co-infection and single-infection. All isolates were resistant to cefotaxime and ceftriaxone. All EAEC isolates carried the blaCTX-M-14 gene and all ETEC isolates the blaCTX-M-15 gene, as detected by multiplex PCR and sequencing analysis. Sequence type and PFGE results indicated three different patterns depending on the O serotype. WGS results of representative isolates revealed that the ETEC O25 strains harbored blaCTX-M-15 located on IncK plasmids associated with the ΔblaTEM-blaCTX-M-15-orf477 transposon. The representative EAEC O44 isolates carried blaCTX-M-14 on the chromosome, which was surrounded by the ISEcp1-blaCTX-M-14-IS903 transposon. To the best of our knowledge, this is the first report of co-infection with chromosomally located blaCTX-M-14 and plasmid-encoding blaCTX-M-15 in pathogenic E. coli. Our findings indicate that resistance genes in clinical isolates can spread through concurrent combinations of chromosomes and plasmids.